Metastatic colorectal cancer and Laetrile in the 21st century: persistence of a 1970s controversy - Nitikman, Michael; Duncan, Katrina; Yoshida, Eric (AME Medical Journal, 2017)
In this case report, we present a common gastroenterological complaint with a unique twist discovered in taking a thorough medical history: a 48-year old man with a history of metastatic colorectal cancer, presented with an upper GI tract bleed. He had recently begun taking Vitamin B17, an alternative therapy purchased in Mexico marketed as an anti-cancer medication. This vitamin is a previously popularized, but ultimately de-bunked and banned substance better known as laetrile. Laetrile was adopted as an alternative cancer therapy in the 1950’s. It was marketed based on small Best Case Series documenting Laetrile-related symptomatic benefits. There have been no randomized clinical trials performed. Twenty years later, Laetrile was banned following multiple reports of toxicity and death. Laetrile use in the 21st century is particularly unique and provides us with an opportunity to reflect on the importance of clinical trials and evidence-based medicine, which guides our daily practice.